TAXONOMY OF TRAINING ACTIVITIES IN THE STUDY OF PSYCHOLOGY - Sadiqova Gulbarno Odiljon kizi (Ecominds Press, 2025)
The article describes the educational activities, technical methods, technologies in teaching psychology, their content, and the opinions of scientists.
Keywords: Learning, learning, technique, method, student, requirement, task, taxonomy, education.